2002
DOI: 10.1002/jsfa.1222
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterisation of enzymatically produced lauric acid esters of fructose

Abstract: Lauric acid esters of fructose were produced using immobilised lipase (EC 3.1.1.3; Novozym 435). A molecular sieve was used to shift the reaction towards the synthesis. The mono-, di-and higher esters of lauric acid with fructose were obtained and analysed qualitatively and quantitatively by highpressure liquid chromatography (HPLC). At a 5:1 molar ratio of lauric acid to fructose the amounts of monoester, diester and higher esters produced were 37, 53 and 98 mg respectively after 96 h of reaction time. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 20 publications
2
9
0
1
Order By: Relevance
“…Therefore it was concluded that the Lipozyme 435 can be effectively used for three batches. Similar results were obtained by Sekeroglu, G. et al in their research work on production and characterization of Isopropyl Laurate using Novozyme 435 Candida antarctica 6 .…”
Section: Reusability Of Enzymesupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore it was concluded that the Lipozyme 435 can be effectively used for three batches. Similar results were obtained by Sekeroglu, G. et al in their research work on production and characterization of Isopropyl Laurate using Novozyme 435 Candida antarctica 6 .…”
Section: Reusability Of Enzymesupporting
confidence: 89%
“…4 . A similar plot of graph which showed a plateau formation after 3-4 hours was obtained by Sekeroglu, G. et al in their research work on production and characterization of Isopropyl Laurate using Novozyme 435 Candida antarctica 6 .…”
Section: Effect Of Timesupporting
confidence: 78%
See 1 more Smart Citation
“…Removal of water pushes the reaction toward forward direction. However, removal of water can be challenging but can be achieved with the help of molecular sieves, salt hydrates, silica gel beads, and vacuum distillation [123]. There are many papers available in the literature on biocatalytically synthesized esters, but most of them have reported the use of organic solvents for synthesis and post-synthesis purification process.…”
Section: Factors Limiting Biocatalytic Synthesis Of Cosmetic Estersmentioning
confidence: 99%
“…Initially, A. awamori K4 b-xylosidase was used to transfer one xylosyl residue to a dihydric alcohol as a M. Kurakake (&) Á Y. Ito Á T. Komaki Department of Life and Nutritional Science, Fukuyama University, 1-985 Sanzo, Higashimura-cho, Fukuyama, Hiroshima 729-0292, Japan e-mail: kurakake@fubac.fukuyama-u.ac.jp linker. This was followed by enzymatic synthesis using lipases (Sekeroglu et al 2002;Plou et al 2002). Linoleic acid was linked to another terminal hydroxyl side of the transfer product through an esterification reaction catalyzed by lipases.…”
Section: Introductionmentioning
confidence: 99%